EFFECT OF CASTING PRACTICE ON THE STORED ENERGY OF COLD WORK AND RECRYSTALLIZATION BEHAVIOR OF AN AL-0.5-PERCENT FE ALLOY - CIGDEM, M (CARL HANSER VERLAG, 1993)
The recrystallisation of a super-pure Al-0.5 % Fe alloy has been investigated using differential scanning calorimetry. Due to the absence of large thermal effects resulting either from precipitation or from dissolution processes, it was possible to measure the stored energy of cold-deformed specimens, released during recrystallisation, by annealing in the calorimeter. Results derived from specimens of permanent-mould and direct-chill cast materials indicate that the stored energy of cold work and the recrystallisation temperature are determined to a large extent by the casting practice-induced microstructural features of the cast slabs which permeate throughout the subsequent processing. It has been shown that the tensile strength, recrystallisation temperature and time, and the stored energy values are higher for ingots solidified at higher cooling rates.
Keywords: COMMERCIAL PURITY ALUMINUM; DEFORMATION; Metallurgy & Metallurgical Engineering